Type of Active Learning Implementation in Science Education: A Systematic Review - Ridani, Maulida; Arianingrum, Retno (Universitas Pendidikan Ganesha, 2024)
Involving students in active learning is associated with positive learning outcomes. Despite the evidence supporting the positive learning outcomes of active learning, the adoption of active learning has been slow. Numerous education researchers have documented their application of active learning. However, there is no research yet that systematically analyzes these studies regarding the type of active learning implementation in science education. This systematic review analysis study was conducted to review the type of active learning implementation in science education. The main criteria for the selection of articles is the implementation of active learning in the field of science education with a period ranging from 2012 to 2022 from the well-known international database. There were 20 articles were obtained that fit into the criteria using the Active Learning keyword. The review was focused on the course, type of active learning, aims, method, samples, and data collection tools. The results show that the most studied course is interdisciplinary chemistry. Active learning types coded Not applicable, Others, Hybrid learning, Group work, Online-based learning, Hands-on Learning, and Inquiry. Articles aim to investigate active learning effects using quantitative methods. Undergraduate student samples enriched these studies, with data collected through surveys and descriptions. These findings can inspire science educators to adopt suitable active learning strategies, impacting students' achievements in science education.